The Constitution in the courts : law or politics? - Perry, Michael J. (Oxford University Press, 1994)
In the modern period of American constitutional law-the period since the U.S. Supreme Court outlawed racially segregated public schooling in Brown v. Board of Education (1954)-there has been a persistent and vigorous debate in the United States about whether the Court has merely been enforcing the Constitution or whether, instead, in the guise of enforcing the Constitution, the Court has really been usurping the legislative prerogative of making political choices about controversial issues. In this book, Professor Perry carefully disentangles and then thoughtfully addresses the various fundamental issues at the heart of the controversy: What is the argument for "judicial review"? What approach to constitutional interpretation should inform the practice of judicial review? How large or small a role should the Court play in bringing the interpreted Constitution to bear in resolving constitutional conflicts? To what extent are the Court's most controversial modern decisions-for example, decisions about racial segregation, discrimination based on sex, abortion, and homosexuality-sound; to what extent are they problematic?; The Constitution in the Courts is a major contribution to one of the most fundamental controversies in modern American politics and law